Efficacy of enhanced HIV counseling for risk reduction during pregnancy and in the postpartum period: a randomized controlled trial. - Suzanne Maman (Public Library of Science (PLoS), 2014)
Introduction Pregnancy and the postpartum period present important intervention opportunities. Counseling can leverage the motivation women have during this time to change behaviors that may negatively affect their health and the heath of their infants. Methods Pregnant women attending an antenatal clinic in South Africa were randomly allocated to treatment (n=733) and control arms (n=747). Treatment arm participants received enhanced HIV pre- and post-test counseling, legal support and access to support groups at baseline, which occurred at the first antenatal visit, and then six and ten weeks postpartum. Control arm participants received standard HIV testing and counseling (HTC) and two postpartum attention control sessions. Outcomes were incidence of sexually transmitted infection (STI) by 14 weeks postpartum and past 30-day inconsistent condom use at 14 weeks and 9 months postpartum. Results There were no intervention effects on incident STIs for either HIV-negative (adjusted risk ratio (aRR) 1.01, 95% CI 0.71-1.44) or HIV-positive participants (aRR 0.86, 95% CI 0.61-1.23). The intervention was associated with a 28% decrease in risk of past 30-day inconsistent condom use at nine-months among HIV-negative women (aRR 0.72,95% CI 0.59-0.88), but did not affect inconsistent condom use among HIV-positive women (aRR1.08; 95% CI 0.67-1.75). Discussion An enhanced counseling intervention during pregnancy and the postpartum period can lead to reductions in inconsistent condom use among HIV-negative women. Results underscore the importance of the counseling that accompanies HIV HTC. More work is needed to understand how to promote and sustain risk reduction among HIV-positive women. Trial registration ClinicalTrials.gov NCT01683461.